2015
DOI: 10.3233/jvr-150748
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality job interview training for veterans with posttraumatic stress disorder

Abstract: BACKGROUND Veterans with posttraumatic stress disorder (PTSD) have low employment rates and the job interview presents a critical barrier for them to obtain competitive employment. OBJECTIVE To evaluate the acceptability and efficacy of virtual reality job interview training (VR-JIT) among veterans with PTSD via a small randomized controlled trial (n=23 VR-JIT trainees, n=10 waitlist treatment-as-usual (TAU) controls). METHODS VR-JIT trainees completed up to 10 hours of simulated job interviews and reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 26 publications
3
49
0
Order By: Relevance
“…The observed improvement in interviewing skills in this cohort is consistent with the evaluation of VR-JIT in other clinical populations (Smith et al, in press-a; Smith et al, 2014a; Smith et al, 2014b). Also, our findings that trainees with schizophrenia had greater odds of receiving job offers and higher doses of training were related to fewer weeks of job searching replicated the results from a recent 6-month follow-up study of a cohort primarily diagnosed with mood disorders or PTSD (Smith et al, in press-b).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The observed improvement in interviewing skills in this cohort is consistent with the evaluation of VR-JIT in other clinical populations (Smith et al, in press-a; Smith et al, 2014a; Smith et al, 2014b). Also, our findings that trainees with schizophrenia had greater odds of receiving job offers and higher doses of training were related to fewer weeks of job searching replicated the results from a recent 6-month follow-up study of a cohort primarily diagnosed with mood disorders or PTSD (Smith et al, in press-b).…”
Section: Discussionsupporting
confidence: 88%
“…Four trainees and three controls with schizophrenia completed prior RCTs of VR-JIT (Smith et al, in press-a; Smith et al, 2014b) and their data were included in all current analyses to optimize statistical power with final sample sizes of n=21 trainees and n=11 controls. Participants were re-contacted after 6 months and asked to complete a follow-up survey.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…75 studies were identified. VR has been used as a form of exposure treatment for: social anxiety disorder [22][23][24][25]; PTSD for military veterans [26,27], world trade centre attack [28] and assault victims [29]; a range of specific phobias, with interest in fear of flying [30,31]and fear of spiders [32][33][34][35][36]; and OCD [37][38][39]. The virtual environments that VR operates within have been the focal point of anxiety research, with some studies looking specifically at the role of audio, visual and bimodal stimuli [40][41][42] Malbos et al [48] found that when treating anxiety for agoraphobia VRET was just as effective in reducing anxiety as VRET with CBT combined.…”
Section: Anxietymentioning
confidence: 99%